CARTOON MOVIE FOR IMPROVING STUDENTS' VOCABULARY: A STUDY ON THE USE OF DORA THE EXPLORER - Maru, Mister Gidion; Lontaan, Michelle Rachel (SoCul: International Journal of Research in Social Cultural Issues, 2024)
The problem in this study began with students of SDN 1 Tondano who were unable to master English, especially vocabulary. The researcher was conducted using an experimental approach, with a sample of grades six consist of 22 students. And the data was obtained through pre-test and post-test during two meetings. The data were analyzed by using SPSS version 23 with an analysis of Paired Sample T-Test to know the significant effect of using media cartoon movies Dora the Explorer in teaching English vocabulary. The result in this study showed that there was significant effect using media cartoon movies in teaching English Vocabulary for two meetings. The significant (2-tailed) score of pre-test and post-test for two meetings was less than 0.05. the researcher concluded that using media cartoon movies in teaching English vocabulary to grades six SDN 1 Tondano was effective.